Experience and Perception of Healthcare Workers on the Challenges of Follow-Up and Treatment of Tuberculosis Patients in Southern Ethiopia: An Exploratory-Descriptive Qualitative Study - Abebe A; Nuriye S; Baza D; Markos M; Woldeyohanes S; Gelgelu TB (Dove Medical Press, 2022)
Amene Abebe,1 Shemsu Nuriye,1 Daniel Baza,2 Mesfin Markos,3 Selamawit Woldeyohanes,1 Temesgen Bati Gelgelu1 1Wolaita Sodo University, School of Public Health, Wolaita Sodo, Ethiopia; 2Wolaita Sodo University, School of Nursing, Wolaita Sodo, Ethiopia; 3Wolaita Sodo University, School of Midwifery, Wolaita Sodo, EthiopiaCorrespondence: Amene Abebe, Email ameneabe@gmail.comBackground: There is a scarcity of research evidence on TB follow-up and treatment challenges from a healthcare worker's perspective in Ethiopia. Therefore, this study aimed to explore and describe the experience and perception of healthcare workers on the challenges of follow-up and treatment of TB patients in Southern Ethiopia.Material and Methods: A qualitative exploratory-descriptive study was employed among 26 purposely selected Healthcare Workers (HCWs) from Wolaita Sodo University-Comprehensive Specialized Hospital and Achura, Boloso Sore, and Tida Health Centers in December 2021 and January 2022. Initially, the maximum variation purposive sampling technique was employed, then based on the data requirement of the study it was enriched by a theoretical sampling method. The required data were collected through one-on-one face-to-face audio-taped in-depth interviews. Data analysis was conducted by using a qualitative data analysis framework for the applied research method. NVivo Software Version 11 was used to ease data organization and analysis. Detailed textual narration of subthemes, and themes was done using direct verbatim quotations in the respective headings and subheadings.Results: In the current study, three major themes and eleven sub-themes emerged from the data. The three major themes include the experience of healthcare workers, perceived challenges, and suggestions for improvement of TB patients' follow-up and treatment. Healthcare worker's experience, compliance with infection prevention protocols, fear of contracting and/or spreading TB, public awareness of TB, socio-economic burdens, providers-related problems, shortage of medical supplies, unconducive physical work environment, provision of holistic support for the patients, provision of in or out of service training, and supportive supervision were the sub-themes.Conclusion: This study explored the multidimensional challenges adjoining follow-up and treatment of TB patients. Regular monitoring and supportive supervision accompanied by appropriate and timely decisions and feedback are vital to ensure effective follow-up and treatment of TB patients in Ethiopia.Keywords: challenges, experience, follow-up, healthcare workers, patients, perception, TB, treatment